2018
DOI: 10.1038/s41598-018-29476-6
|View full text |Cite
|
Sign up to set email alerts
|

A Photonic Switch Based on a Hybrid Combination of Metallic Nanoholes and Phase-change Vanadium Dioxide

Abstract: A photonic switch is an integral part of optical telecommunication systems. A plasmonic bandpass filter integrated with materials exhibiting phase transition can be used as a thermally reconfigurable optical switch. This paper presents the design and demonstration of a broadband photonic switch based on an aluminium nanohole array on quartz utilising the semiconductor-to-metal phase transition of vanadium dioxide. The fabricated switch shows an operating range over 650 nm around the optical communication C, L,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…The phase-transition and phase-change materials have enabled a wide variety of metasurface devices [151]. VO 2 has been applied to the frequency control of plasmonic antenna arrays [152][153][154][155], free-space phase [156,157], amplitude [158][159][160][161][162] and polarization [163] modulators, plasmonic color generation [164,165], adaptive thermal camouflage [166], tunable absorbers and emitters [167][168][169][170][171], and free-form metadevices [134]. Compared to VO 2 , chalcogenide O-PCMs exemplified by GST offer even larger optical contrast in the near-IR and UV spectral regimes with an index change up to 2.8 [172][173][174][175][176].…”
Section: Optical Phase-change Mediamentioning
confidence: 99%
“…The phase-transition and phase-change materials have enabled a wide variety of metasurface devices [151]. VO 2 has been applied to the frequency control of plasmonic antenna arrays [152][153][154][155], free-space phase [156,157], amplitude [158][159][160][161][162] and polarization [163] modulators, plasmonic color generation [164,165], adaptive thermal camouflage [166], tunable absorbers and emitters [167][168][169][170][171], and free-form metadevices [134]. Compared to VO 2 , chalcogenide O-PCMs exemplified by GST offer even larger optical contrast in the near-IR and UV spectral regimes with an index change up to 2.8 [172][173][174][175][176].…”
Section: Optical Phase-change Mediamentioning
confidence: 99%
“…Kats et al have shown that the mid‐infrared plasmonic response of nanoantenna arrays can be modulated by using the index change of an underlying VO 2 substrate in proximity to its phase transition . Recent studies showed that, via direct thermal control, dynamically manipulated plasmonic color ( Figure a), extinction ratio, and polarization state of light (Figure 3b) can be achieved in hybrid metasurfaces integrated with VO 2 nanostructures.…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…Consequently, VO 2 films have been introduced into photonic metasurfaces as a substrate that provide a highly variable dielectric environment . Nevertheless, to enable tunable responses in more sophisticated systems based on the IMT of VO 2 , the fabrication of VO 2 on other materials, including those in an amorphous phase, is desirable. For instance, to enable the active response regulation of metasurface absorbers that typically consist of three (metal/dielectric/metal) layers, VO 2 films must be grow on metallic or other amorphous thin films.…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…of the dielectric multilayer before the plasmonic layer is added. The plasmonic filter comprises an array of nanoholes in a hexagonal arrangement [ 38 ] inserted in the 150 nm Au film. Figure 5a shows the normalized electric field of the surface plasmons in the hole array (top view) at peak wavelengths for NIR 1–5.…”
Section: Design Of Hybrid Multispectral Filtersmentioning
confidence: 99%